The cannabinoid CB1 receptor and mTORC1 signalling pathways interact to modulate glucose homeostasis in mice - Bermúdez Silva, Francisco Javier; Romero-Zerbo, Silvana Yanina; Haissaguerre, Magalie; Ruz-Maldonado, Inmaculada; Lhamyani, Said; El-Bekay, Rajaa; Tabarin, Antoine; Marsicano, Giovanni; Cota, Daniela (The Company of Biologists, 2016)
The endocannabinoid system (ECS) is an intercellular signalling mechanism that is present in the islets of Langerhans and plays a role in the modulation of insulin secretion and expansion of the β-cell mass. The downstream signalling pathways mediating these effects are poorly understood. Mammalian target of rapamycin complex 1 (mTORC1) signalling is a key intracellular pathway involved in energy homeostasis and is known to importantly affect the physiology of pancreatic islets. We investigated the possible relationship between cannabinoid type 1 (CB1) receptor signalling and the mTORC1 pathway in the endocrine pancreas of mice by using pharmacological analysis as well as mice genetically lacking the CB1 receptor or the downstream target of mTORC1, the kinase p70S6K1. In vitro static secretion experiments on islets, western blotting, and in vivo glucose and insulin tolerance tests were performed. The CB1 receptor antagonist rimonabant decreased glucose-stimulated insulin secretion (GSIS) at 0.1 µM while increasing phosphorylation of p70S6K1 and ribosomal protein S6 (rpS6) within the islets. Specific pharmacological blockade of mTORC1 by 3 nM rapamycin, as well as genetic deletion of p70S6K1, impaired the CB1-antagonist-mediated decrease in GSIS. In vivo experiments showed that 3 mg/kg body weight rimonabant decreased insulin levels and induced glucose intolerance in lean mice without altering peripheral insulin sensitivity; this effect was prevented by peripheral administration of low doses of rapamycin (0.1 mg/kg body weight), which increased insulin sensitivity. These findings suggest a functional interaction between the ECS and the mTORC1 pathway within the endocrine pancreas and at the whole-organism level, which could have implications for the development of new therapeutic approaches for pancreatic β-cell diseases.
Keywords: Insulina; Cannabinoids; Insulin secretion; Rapamycin; Rimonabant; Islets; CB1; S6K1